The long arm of the neoliberal leviathan in the counter-trafficking field: the case of Portuguese NGOs - Clemente, M. (International Review of Sociology, 2021)
In recent decades, in many countries including Portugal, human trafficking has become an important issue on political agendas, attracting increased investment of financial and human resources, and the growing involvement of civil society organizations. Employing a historical perspective, this article analyses the role of non-governmental organizations (NGOs) in the counter-trafficking field, in particular, in the conceptualization of human trafficking, the elaboration of counter-trafficking policies and practices, and NGOs’ potentials and limitations in challenging them. Using data obtained through prolonged empirical research, the article argues that in contexts characterized by a high level of institutionalization and structural weakness in organized civil society, NGOs have little chance to assume a role beyond serving as a long arm of the neoliberal state apparatus. Both the outsourcing of certain counter-trafficking services to NGOs and the controversial yet undisputed national security-focused approach to trafficking represent integral parts of the practical logics of the counter-trafficking field, which remains largely unquestioned by counter-trafficking NGOs. These logics include the silencing of any debate about prostitution, at least within the Portuguese counter-trafficking apparatus.